COMPARATIVE STUDY BETWEEN ULTRASONOGRAPHIC FINDINGS AND OPERATIVE FINDINGS IN PATIENTS WITH COMMON SURGICAL CONDITIONS OF GALLBLADDER REQUIRING EXPLORATION (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Gallbladder diseases are among the most common surgical conditions requiring operative intervention. Ultrasonography (USG) is the preferred initial imaging modality for diagnosing gallbladder pathology due to its non-invasive nature, accessibility, and cost-effectiveness. However, the accuracy of ultrasonographic findings compared with operative findings requires continuous evaluation. Aims and objectives: Ultrasonography is a widely available, non-invasive, and cost-effective diagnostic tool for gallbladder diseases, with a reported accuracy of 90–95%. This study aims to assess its diagnostic accuracy in chronic gallbladder diseases by comparing ultrasonographic findings with operative findings. Materials and Methods: The study population consisted of 100 patients presenting with common surgical conditions of the gallbladder, diagnosed on clinical and ultrasonographic evaluation and admitted to M.G.M Medical College & L.S.K Hospital, Kishanganj for surgical management and exploration. Results: Most patients were aged 41–60 years (56.0%). Pain abdomen was the commonest symptom (70.0%–100.0%). Leukocytosis was seen in 90.0% and raised ESR in 16.0%. Ultrasonography detected gallstones in 100.0% with wall thickening in 70.0%, AP diameter >3 cm in 76.0%, Murphy’s sign in 60.0%, and choledocholithiasis in 2.0%. Conclusions: Ultrasonography is a highly reliable diagnostic tool for evaluating common surgical gallbladder diseases and demonstrates strong correlation with operative findings. While it accurately detects gallstones and inflammatory changes, certain intraoperative features may be underestimated. Combining clinical assessment with ultrasonographic evaluation can improve preoperative planning and surgical outcomes.